(untitled) (Journal of the Spanish Institute for Strategic Studies, 2021)
The achievement of a coordinated industrial defence policy of the Member States of the European Union is essential to achieve the objective of articulating a genuine Common Security and Defence Policy (CSDP). In recent years, an institutional and financial system has been set up aimed at implementing this industrial policy within the framework of Permanent Structured Cooperation (PESCO) in the area of security and defence policy, established in December 2017. Nevertheless, this development must preserve the principle of coherence, which has been considered regularly as one of the backbone of the efforts of the European Union in its process of functional integration. This doctrinal contribution aims at bringing clarity to the efforts made to settle the foundations of a truly European defence industry, as well as newly opportunity windows for the Spanish landscape.